Non-Trivial Transport Interface in a Hybrid Topological Material With Hexagonal Lattice Arrangement - Du, Lianlian; Liu, Yahong; Li, Meize; Ren, Huiling; Song, Kun; Zhao, Xiaopeng (Frontiers in Physics, 2020)
In this paper, a hybrid topological material with hexagonal lattice arrangement is proposed, consisting of six metal cylindrical resonators and a dielectric slab. As a unit cell, the six metal cylindrical resonators satisfying the C6 symmetry are selected, and the cylindrical resonators are inserted in the dielectric slab. It is demonstrated that a double Dirac cone is created at the Γ point in the proposed topological material. Since the topological effects of the proposed system can be invoked merely by varying the geometric parameters of the unit cell, two band gaps with different topological characteristics can be easily achieved. It is further demonstrated that the topologically protected edge states can be obtained by connecting the two types of lattices with different topological characteristics. Finally, we implement a sharp bend waveguide by using these two types of the topological lattices. It is demonstrated that electromagnetic waves can propagate robustly along the sharp bend interface.